Nitrate Storage and Dissimilatory Nitrate Reduction by Eukaryotic Microbes - Kamp, Anja; Høgslund, Signe; Risgaard-Petersen, Nils; Stief, Peter (Frontiers in Microbiology, 2015)
The microbial nitrogen cycle is one of the most complex and environmentally important element cycles on Earth and has long been thought to be mediated exclusively by prokaryotic microbes. Rather recently, it was discovered that certain eukaryotic microbes are able to store nitrate intracellularly and use it for dissimilatory nitrate reduction in the absence of oxygen. The paradigm shift that this entailed is ecologically significant because the eukaryotes in question comprise global players like diatoms, foraminifers, and fungi. This review article provides an unprecedented overview of nitrate storage and dissimilatory nitrate reduction by diverse marine eukaryotes placed into an eco-physiological context. The advantage of intracellular nitrate storage for anaerobic energy conservation in oxygen-depleted habitats is explained and the life style enabled by this metabolic trait is described. A first compilation of intracellular nitrate inventories in various marine sediments is presented, indicating that intracellular nitrate pools vastly exceed porewater nitrate pools. The relative contribution by foraminifers to total sedimentary denitrification is estimated for different marine settings, suggesting that eukaryotes may rival prokaryotes in terms of dissimilatory nitrate reduction. Finally, this review article sketches some evolutionary perspectives of eukaryotic nitrate metabolism and identifies open questions that need to be addressed in future investigations.